(untitled) (Swiss Medical Weekly, 2025)
BACKGROUND: There is a scarcity of studies that examined the impact of the COVID-19 pandemic on different primary paediatric health services beyond the first pandemic year and with longitudinal analytical approaches. Concerning Switzerland, studies are also lacking that assessed the impact of the pandemic on primary paediatric health services with objective and representative data. The current study addresses these research gaps. METHODS: Representative Swiss health insurance data (covering 96% of the population) of 0–18-year-olds, aggregated by month and by age groups 0–5, 6–10, 11–15 and 16–18 years were used for the analyses. The study period was from January 2018 to March 2022. Interrupted time-series models were applied to compare pandemic and pre-pandemic health care utilisation. The first lockdown served as the point of differentiation between these two periods. Regular visits, urgent visits, well-child visits and telephone consultations as well as routine vaccinations in the primary care setting were used as outcomes. RESULTS: Among 0–5-year-olds, the average utilisation rates of regular, urgent and well-child visits were statistically significantly lower during the pandemic compared to the pre-pandemic period. This decrease in utilisation was primarily due to an initial marked drop after the lockdown, followed by a partial recovery during the pandemic phase. Additionally, the average vaccination rates for measles/mumps/rubella were statistically significantly lower during the pandemic for this age group, without indication of a catch-up over the pandemic phase. For 6–10-year-olds, a decreased average utilisation of regular and urgent visits was found without a statistically significant recovery over the pandemic period. No statistically significant changes were shown for older age groups regarding regular or urgent visits. However, telephone consultations showed statistically significantly higher average utilisation rates during the pandemic compared to the pre-pandemic phase across all age groups. CONCLUSIONS: Delayed or missed well-child visits, which might persist even after a certain recovery, pose the risk of delayed detection of clinical/developmental abnormalities. Furthermore, missed vaccinations for measles/mumps/rubella increase the likelihood of infections and outbreaks, which can be particularly dangerous for the youngest children. Therefore, promoting catch-up well-child visits and vaccinations is essential. Higher utilisation of telephone consultations during the pandemic may have partially compensated the underutilisation of face-to-face consultations/visits in young children. In adolescents, in whom no changes in the utilisation of face-to-face consultations were observed, the increased use of telephone consultations may indicate an increase in health concerns within this age group.